Pengaruh Arus Kas Operasi dan Fixed Assets Intensity terhadap Revaluasi Aset Tetap - Yuki Mayumi Yorianti,; Farah Dalila,; Elvara Kristyariska,; Dita Indah Pratiwi, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Valuation of fixed assets is one of the important issues in fixed asset accounting. The value of the asset becomes irrelevant if the use of the acquisition price does not reflect the actual value of the asset. The issuance of IFRS convergence PSAK uses the fair value of fixed assets to reflect the latest prices so that the asset value will be higher. Therefore, financial reports will provide more relevant information to users of financial reports to serve as a basis for decision making. The method used in this study is a structured review or review method so that it can identify what factors can affect the revaluation of fixed assets. The method of searching for article data sources is done through Google Scholar (2017-2022) which provides articles of scientific writing that are relevant to this research. Based on the results of a literature review of 30 articles or journals, it was revealed that a decrease in some of the operating cash flows had a positive and not significant effect on the revaluation of fixed assets. The intensity of fixed assets partially has a positive and significant effect on the revaluation of fixed assets.